KVANTITATIVNE PROMJENE MORFOLOŠKIH KARAKTERISTIKA I MOTORIČKIH SPOSOBNOSTI DJEČAKA PREDŠKOLSKE DOBI PRIMJENOM PROGRAMA ELEMENTARNIH IGARA U VODI I NA SUHOM - Halid Redžić; Šemsudin Džeko (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The study was conducted on one hundred and fifty boys to school age. Morphologic characteristics described by fifteen variables, and the area of motor abilities with seventeen variables. Application of the canonical discriminant analysis the quantitative changes caused by applying a one-year program of elementary games in the water and on land. The main objective of this study is to improve the morphological and motor status of boys to school age. The criterion for discriminant variable is the strength of applied Wilks lambda. Interpretation was based on the established structures of statistically significant discriminant variables, and relevant centroid position and characteristics of respondents compared to belong control or experimental group.